Improving the Efficiency of Cloud Computing Services Using Cuckoo Search and Bee Colony Algorithms - Mojtaba Aliabadian (Journal of Global Pharma Technology, 2017)
Nowadays, the tendency of organizations to use service-orientation instead of using applications is being increased day by day. Existence of port for the organizations and providing organizational services in frame of web services has enables users to use organizational services rapidly and easily via internet. The basic and initial services of the organization are provided for the users in frame of web services and through the organizational port. Cloud computing as a common computing model for the organizations and firms and even individuals is based on two types of servicing: the deployment location and the type of service provided. In order to meet needs of applicants in best way and to adjust the services rapidly with changed requirements, the services are combined to utilize capability of several available services within the organization or other organizations. In the issues of combining cloud services, one of the most important challenges is the issue of implementation time. As various services are existed in the cloud distributed space, the pace of the problem is large and selecting the optimal option is complicated and time-consuming in most cases. In this study, a new approach is presented for combination of services in cloud computing. The main objective of the proposed method is improvement of efficiency and reduction of implementation time for optimal selection of services available in cloud and consequently, combination of these services. Combination of the services in proposed method is done using combination of Cuckoo Search and Bee Colony Algorithms as the most important meta-heuristic in field of optimization. The way of using these algorithms in frame of proposed method to combine the services in cloud computing is presented in details and practical evaluation is also presented. The simulation results show that the proposed method could provide considerable improvement in field of efficiency criteria compared to similar algorithms.Keywords: Cloud computing, Cloud services combination, Cuckoo Search Algorithm, Bee Colony Algorithm.